2020
DOI: 10.1111/rda.13738
|View full text |Cite
|
Sign up to set email alerts
|

LncWNT3‐IT affects the proliferation of Sertoli cells by regulating the expression of the WNT3 gene in goat testis

Abstract: Contents The proliferation and differentiation ability of testicular Sertoli cells directly affects spermatogenesis and male reproductive development. WNT proteins are involved in the regulation of cell proliferation, differentiation and spermatogenesis. Therefore, to study whether lncRNAs, which regulate the expression of WNT proteins during cell proliferation and differentiation, are worthwhile. In this study, testicular tissue from the Dazu black goat (Capra, goat, Chongqing, China) at neonatal time (less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…LncRNAs was longer than 200 nt, which could not be translated into any protein, but could regulate the expression of target genes and function in multiple biological processes [ 56 ]. Recently, lncWNT3-IT has been shown to regulate WNT3 expression and affect proliferation of goat SCs, confirming the vital function of lncRNAs in SCs [ 57 ]. In the present study, we identified ten thousands of lncRNAs (most are novel), providing useful information to further elucidate their functions in porcine iSCs.…”
Section: Discussionmentioning
confidence: 91%
“…LncRNAs was longer than 200 nt, which could not be translated into any protein, but could regulate the expression of target genes and function in multiple biological processes [ 56 ]. Recently, lncWNT3-IT has been shown to regulate WNT3 expression and affect proliferation of goat SCs, confirming the vital function of lncRNAs in SCs [ 57 ]. In the present study, we identified ten thousands of lncRNAs (most are novel), providing useful information to further elucidate their functions in porcine iSCs.…”
Section: Discussionmentioning
confidence: 91%
“…Experimental reduction of the expression of lncRNA H19 significantly down-regulated the expression levels of IGF-1R in cattle mGSCs [110]. Another study showed that the expression of lncWNT3-IT could affect spermatogenesis in goats [36]. LncWNT3-IT is expressed in Sertoli cells and is related to the WNT3 protein which regulates proliferation and differentiation in testicular Sertoli cells [117,118].…”
Section: Lncrnas In Livestockmentioning
confidence: 99%
“…In goat testes, the proliferation of Sertoli cells was shown to be upregulated with increased expression levels of WNT3 producing overexpression of lncWNT3-IT. In a previous study, He et al [36] showed that lncWNT3-IT enhances WNT3 gene expression by clustering near to the WNT3 gene promoter and modulates the translation of WNT3 in a cis-acting manner, thereby regulating the growth cycle in goat Sertoli cells. Another lncRNA, lncNONO-AS, has been identified in goat testes.…”
Section: Lncrnas In Livestockmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have confirmed that lncRNAs are associated with brown fat formation ( Alvarez-Dominguez et al, 2015 ), skeletal muscle development ( Sun et al, 2016 ), and cashmere growth ( Wang et al, 2017 ). In 2020, He et al (2020) proposed that LncWNT3-IT can promote the proliferation of goat Sertoli cells by positively regulating the expression of the WNT3 gene. In addition, lncRNAs are also involved in the regulation of diseases.…”
Section: Introductionmentioning
confidence: 99%